Sport-related accident as etiology of maxillofacial injuries : A serial case report - Putra, I-Gd-Pt WA.; Gazali, Mohammad; Basyar, Husnul (Hasanuddin University, 2025)
Introduction: Sports-related maxillofacial injuries contribute a significant proportion of the workload in a maxillofacial unit. The aim of this study was to identify the incidence of maxillofacial sports-related injuries, treatments required, and assess the impact of the injury on future sport participation and highlights management dental procedures and jaw stabilization techniques such as IDW Erich Arch Bar.Case Report: A 21-year-old male playing futsal fell, loose teeth. A 13-year-old male playing football collided with another player, sustaining loose teeth and lip lacerations. Treatment involved wound debridement, laceration suturing, and referral to the Dental Conservation Department for further dental trauma management. Wound debridement and laceration suture were followed by repositioning of teeth, fixation teeth. Maxilla and Mandibular trauma was fixated using an interdental wire (IDW) Erich Arch-Bar.Discussion: Athletes frequently suffer maxillofacial injuries due to the physical nature of sports. The mechanism of injury was reported in relation to collision with opponent, impact with equipment or ground/environment.. The most common cause of injury was collision with another player. Differences in the prevalence of various sports, and indeed sporting cultures and traditions may account for the wide range of incidence and etiologies of sports injuries in different countries Conclusion: These cases demonstrate sports-related facial injuries and the importance of proper management, including wound care, dental procedures, and jaw stabilization. The findings emphasize preventive measures in sports to minimize such injuries.